Systematic investigation on the electrochemical performance of Cd-doped ZnO as electrode material for energy storage devices. (February 2022) - Angelin, M. Dhivya; Rajkumar, S.; Ravichandran, A.T.; Merlin, J. Princy
Abstract: Many researchers have focused on enhancing the performance of energy storage devices to satisfy the growing demand for energy worldwide. This paper is an attempt to tune the capacitive behavior of pristine ZnO through its Cd doping via the simple synthetic method. To examine their electrochemical behavior, samples of modified ZnO with three concentrations of the dopant (Cd) (3, 6, and 9 wt% Cd-doped ZnO) were prepared. The as-prepared products were characterized by spectral as well as analytical techniques. The 9 wt% Cd-doped ZnO electrode, featuring fast electrolyte permeation and rich electrochemically active sites, showed an excellent specific capacitance (Csp) of 627 Fg −1  at a current density of 1 Ag -1 and substantial cycling stability of 93.3% even after 5000 GCD cycles. The addition of dopants enhanced electrical conductivity due to effective charge transfer and electron transport. The unique nanorod-like structure was found to be responsible for the exceptional electrochemical properties of the samples. Until now, there were no reports on Cd-doped ZnO nanorods as electrode material for supercapacitors. This work provides a simple and cost-effective method for fabricating a 9 wt% Cd-doped ZnO electrode, which may open up new possibilities for efficient electrodes in next-generation supercapacitors. Graphical abstract: Image 1 Highlights: Bare ZnO as well as 3, 6, and 9 wt% Cd-doped ZnO were prepared by a simple chemical method. The as-fabricated 9 wt% Cd-doped ZnO electrode exhibited a good Csp (627 F g −1 at 1 A g −1 ). The 9 wt% Cd-doped ZnO exhibited an excellent electrochemical stability of 93.3% after 5000 GCD cycles. The findings pave the way for future applications in cost-effective synthesis routes that make these materials industrially viable for use in alternative energy storage devices.